PSYCHOPEDAGOGICAL PROBLEMS OF EMOTIONAL BURNOUT SYNDROME IN TEACHERS AND STUDENTS - Muradova Natiq Qizi, Sabina; Bayramov Bashir Oglu, Matlab (Revista Gênero e Interdisciplinaridade, 2025)
This article explores the psychopedagogical problems associated with emotional burnout syndrome in teachers and students. Emotional burnout, characterized by chronic fatigue, emotional exhaustion, and decreased motivation, has become a significant concern in educational settings. The study aims to identify the causes and mechanisms of burnout, its impact on professional performance, and the importance of teacher-student relationships in mitigating burnout effects. Through a comprehensive literature review and qualitative analysis, the findings highlight the prevalence of burnout in educational environments and suggest strategies for prevention and intervention.